2019
DOI: 10.1152/ajpgi.00403.2017
|View full text |Cite
|
Sign up to set email alerts
|

RNA regulons are essential in intestinal homeostasis

Abstract: Intestinal epithelial cells are among the most rapidly proliferating cell types in the human body. There are several different subtypes of epithelial cells, each with unique functional roles in responding to the ever-changing environment. The epithelium’s ability for rapid and customized responses to environmental changes requires multitiered levels of gene regulation. An emerging paradigm in gastrointestinal epithelial cells is the regulation of functionally related mRNA families, or regulons, via RNA-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“… 3 Recent studies demonstrated the key contribution of several RBPs in the control of intestinal epithelial cell homeostasis and in response to injury. 4 Among the different pathways involved in CRC, a series of evidence have highlighted that colon tumor cells highjack posttranscriptional mechanisms that enable a fast and robust adjustment of protein expression in response to intrinsic and extracellular signals, leading to cell adaptation to the local microenvironment. 5 Dysregulated RBPs influence the expression and function of pro-tumorigenic and tumor-suppressor proteins, among others.…”
mentioning
confidence: 99%
“… 3 Recent studies demonstrated the key contribution of several RBPs in the control of intestinal epithelial cell homeostasis and in response to injury. 4 Among the different pathways involved in CRC, a series of evidence have highlighted that colon tumor cells highjack posttranscriptional mechanisms that enable a fast and robust adjustment of protein expression in response to intrinsic and extracellular signals, leading to cell adaptation to the local microenvironment. 5 Dysregulated RBPs influence the expression and function of pro-tumorigenic and tumor-suppressor proteins, among others.…”
mentioning
confidence: 99%
“…The rapidity with which intestinal epithelium must respond to environmental stressors suggests a necessity for multiple layers of gene regulation. RNA binding proteins have emerged as critical regulators of intestinal proliferation and stem cell dynamics [1][2][3][4][5][6][7]. IGF2 mRNA-binding protein 1 (IMP1, IGF2BP1) is an RNA binding protein with roles in mRNA trafficking, localization, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided evidence that RBPs are abnormally expressed in cancer relative to adjacent normal tissues and their expression correlates with patients' prognosis [9]. Recent studies have revealed the key contribution of several RBPs in the control of intestinal epithelial cell homeostasis [10]. A series of evidences have highlighted that tumour cells, including CRC cells, are able to highjack a series of post-transcriptional mechanisms in response to intrinsic and extracellular signals, leading to cell adaptation to the local microenvironment [8].…”
Section: Introductionmentioning
confidence: 99%